Níveis de farelo de algodão de alta energia em suplementos múltiplos para bovinos em pastejo: Desempenho e avaliação econômica1 - Zervoudakis, Joanis Tilemahos; Zanin, Rafaela; Pesqueira-Silva, Lilian Chambó Rondena; Hatamoto-Zervoudakis, Luciana Keiko; Cabral, Luciano Da Silva; Benatti, João Marcos Beltrame [UNESP]; Da Silva-Marques, Renata Pereira (Universidade Estadual de Londrina, 2015)
The objective was to evaluate the substitution levels of protein from soybean meal by high energy cottonseed (CS) meal in multiple supplements for beef cattle grazing in the dry season on the average daily gain (ADG) and economic viability. Twenty Nellore steers with initial body weight of 351.25±35.38 kg and average initial age of 24±0.8 months were used, divided into four paddocks of Brachiaria brizantha cv. Marandu with 1.6 ha each incompletely randomized design with four animals and five supplements to assess the following supplements: 0CS, 25CS and 50CS corresponding to the level of 0,25 and 50% high energy cottonseed meal to replace the meal soybean, provided the amount of 2 kg/animal/day, which were compared to mineral mixture (MM). The supplement 25CS provided higher (P<0.0001) ADG (0.75kg/animal/day-1) compared to supplement 50CS (0.60kg/animal/day-1). The ADG of animals supplemented with 0CS (0.53kg/animal/day-1) did not differ (P<0.0001) of the ADG of the bulls receiving supplementation with 25CS (0.75k /animal/day-1) and 50CS (0,60kg / animal / day-1). The 25CS supplement showed a higher economic return on invested capital in the period. The use of cottonseed meal high energy level of 25% replacement of soybean meal in multiple supplements provided greater weight gain of cattle and improved economic viability.
Levels of high energy cottonseed meal in multiple supplements for grazing cattle: Performance and economic evaluation
Keywords: Cattle; Dry period; Marandu; Protein; Supplementation